Analytical and experimental study on dissolved pollutant wash‐off over impervious surfaces. Issue 25 (19th November 2017) - Xiao, Yang; Zhang, Taotao; Wang, Lei; Liang, Dongfang; Xu, Xingwu
Abstract: Non‐point source pollution in the impervious surface of city, which including dissolved and particulate pollutants, is a significant source of water pollution. Simple first‐order decay models can generally simulate the cumulative wash‐off process of the particulate pollutants. There is inadequate knowledge as to whether or not they are suitable for dissolved pollutants. This study presents a mathematical wash‐off model for dissolved pollutants, which combines analytical equations for overland flows and the exponential equation for the pollutant wash‐off. A series of laboratory experiments have been conducted to verify this wash‐off model. It shows that the pollutant concentration and pollutant transport rate can be predicted well by the newly developed equations. It is found that the pollutant concentration monotonically decreases to zero as the accumulated pollutants are washed off, whereas the pollutant transport rate first increases to the maximum value and then decreases to zero. The maximum pollutant transport rate is found to increase with the decrease of the arrival time of the maximum value. The difference between the simplified exponential model and the amended wash‐off equation depends on the initial residual percentage ( P c ), but the present equation generally provides a more accurate representation of the wash‐off process of dissolved pollutants.